Electrochemical Nitrate Reduction with Low-Index Cu Single Crystals: Selectivity Trends in Alkaline Solution - William T. Phillips; Hongshan Bi; Anastasija Vasilijević; Owen P. Doyle; Zhou Lin; Joseph S. DuChene (Journal of the American Chemical Society, 2026)
Abstract Electrochemical nitrate (NO3−) reduction is a promising pathway toward the production of ammonia (NH3). While copper (Cu) electrodes are commonly used for this reaction, the influence of Cu surface structure on reaction selectivity is poorly understood. Here, we performed electrochemical NO3− reduction in alkaline electrolytes with Cu(100), Cu(110), and Cu(111) single-crystal electrodes and quantified the product distributions across a range of applied potentials. Our systematic study of electrocatalytic NO3− reduction demonstrated that the Cu(100) and Cu(110) surfaces exhibited similar selectivity and rates for NH3 production, but the Cu(100) surface provided >95% Faradaic efficiency toward NH3 over the broadest range of applied potentials. In contrast, the Cu(111) surface was significantly less selective for NH3 production. Further comparing the electrochemical behavior of Cu single crystals to their corresponding product distributions revealed that nitrite (NO2−) reduction voltammograms were strong predictors of electrocatalytic performance for all three low-index Cu surfaces in alkaline electrolytes. Quantum mechanical calculations indicate that the Cu(100) surface exhibits the lowest potential-determining step for NO3− reduction to NH3, supporting our experimental findings. Detailed analysis of metal−adsorbate interactions also revealed the role of Cu surface structure in stabilizing key reaction intermediates to promote selective NH3 production. Our combined experimental and computational study establishes electrocatalytic selectivity of low-index Cu facets for NH3 synthesis and offers practical guidelines for the design of Cu-based electrocatalysts capable of selective electrochemical NO3− reduction in alkaline solutions.